Body Image and Its Impact on Psychological Stress Among Pregnant Women in the Era of Social Media - Sundari, Sundari; Sari, Rury Narulita; Iztiqomah, Lailatul (FORIKES, 2026)
Physical changes during pregnancy often lead to negative perceptions of body shape or body image, particularly in the era of social media, which reinforces unrealistic beauty standards. Such conditions may increase pregnant women’s vulnerability to psychological stress, ultimately affecting maternal health. This study aims to analyze the correlation between body image and psychological stress among pregnant women in the social media era. An analytical approach with a cross-sectional design was employed, involving 66 pregnant women in their first to third trimesters who were active social media users. Data were collected using a modified version of the Body Shape Questionnaire [BSQ‑16) and the Perceived Stress Scale [PSS‑10). Data analysis was conducted using the Pearson Product Moment correlation test. The results showed that the mean scores for body image and psychological stress were 56.81 and 73.86, respectively. The hypothesis testing yielded a p‑value of 0.001, indicating a significant correlation between body image and psychological stress levels among pregnant women. It is therefore concluded that negative perceptions of bodily changes during pregnancy contribute to increased psychological stress in pregnant women in the era of social media.Keywords: body image; psychological stress; pregnant women; social media